PERANCANGAN IDENTITAS VISUAL TOKO ROTI DARI DARI - Nathaniel Tegar Prakasa; Anggi Anggarini; Yoga Putra Pratama (Universitas Trisakti, 2023)
The Dari Dari's Bakery Visual Identity Design. The bakery business is highly attractive to entrepreneurs in Indonesia because of the prevalent breakfast culture, where bread is a popular choice for morning meals. Among the many bread brands in Indonesia, Dari Dari, a small and medium-sized enterprise (UKM), stands out with its focus on bakery and pastry products made from natural ingredients without artificial additives. To strengthen its brand identity and market appeal, Dari Dari is undergoing a visual identity design process, aiming to create a unique logo and extend it to other promotional media. The research involves qualitative and quantitative methods such as literature studies, observations, interviews, and questionnaires to effectively convey the brand's message and values to customers and establish a distinct position in the competitive market. Keywords: visual identity, logo, UKM, bakery